Outbreak of Cholera in the Republic of Congo and the Democratic Republic of Congo and the global picture - Kelvin, Alyson Ann (The Journal of Infection in Developing Countries, 2011)
Cholera is an acute intestinal disease caused by infection of the Vibrio cholerae bacterium. Often manifested as a constant diarrhoeal disease, Cholera is associated with significant mortality as well as economic loss due to the strain on health care. Cholera often affects nations with lower economic status. The recent outbreak of cholera in the Republic of Congo and the Democratic Republic of Congo has affected thousands of people. Here we review the past cholera epidemiology, molecular mechanisms of the bacterium, and the political and environmental aspects that affect the treatment and eradication of this disease.